2005
DOI: 10.1159/000086079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oxidative Stress in the Early Posttransplant Period: Comparison of Cyclosporine A and Tacrolimus-Based Regimens

Abstract: Background: Oxidative stress is one of the leading causes of cardiovascular morbidity and mortality in chronic kidney disease. Although it is clear that many metabolic abnormalities improve, the effects of kidney transplantation on oxidative state are obscure. Methods: Twenty-three kidney transplant patients were included in the study. Eleven patients (mean age 27.9± 9.1 years) were treated with cyclosporine A (CsA) whereas 12 patients (mean age 22.4 ± 3.4 years) were treated with tacrolimus. Twenty-three heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
3
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 63 publications
1
37
3
1
Order By: Relevance
“…10 In a short-term study, Vural and associates found a reduction in malondialdehyde levels in both cyclosporine-and tacrolimus-treated patients 28 days after transplant. 31 These results conflict with our results, as we demonstrated an increase in malondialdehyde levels even at 30 days after transplant. When both groups of calcineurin inhibitors were compared, oxidative stress reached the maximal level in the sixth month after transplant in the cyclosporine-treated group and in the third month after transplant in the tacrolimus-treated group.…”
Section: Discussioncontrasting
confidence: 99%
“…10 In a short-term study, Vural and associates found a reduction in malondialdehyde levels in both cyclosporine-and tacrolimus-treated patients 28 days after transplant. 31 These results conflict with our results, as we demonstrated an increase in malondialdehyde levels even at 30 days after transplant. When both groups of calcineurin inhibitors were compared, oxidative stress reached the maximal level in the sixth month after transplant in the cyclosporine-treated group and in the third month after transplant in the tacrolimus-treated group.…”
Section: Discussioncontrasting
confidence: 99%
“…A 28-day study described improvement in oxidative status parameters, TBARS decreased and SOD and GPX activities increased during the posttransplantation period. 20 As shown in Table 3, we found no effect of renal transplantation on the activity of either enzyme (CAT or SOD). There is also a disagreement on the results for lipid peroxidation.…”
Section: Discussionmentioning
confidence: 51%
“…4,8,10,[16][17][18][19][20][21][22][23][24] Our earlier trials were focused on changes in OS caused by calcineurin inhibitors in the posttransplantation period by evaluation of AOPP levels. 24,16 In this study, we examined the effects of KT on selected components of the antioxidant defence system in parallel with biochemical and hematological parameters over 6 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…42 Oxidative stress may decrease by 28 days after kidney transplant; however, although MDA levels are decreased, erythrocyte superoxide dismutase and glutathione peroxidase levels increase with decreased serum creatinine levels, and this effect is similar in patients treated with tacrolimus or cyclosporine. 16 Tacrolimus or cyclosporine cause comparable oxidative stress at the cellular level in patients who have hypertension after kidney transplant. 43 At 6 months after the kidney transplant, patients receiving tacrolimus or cyclosporine have increased MDA levels.…”
Section: Discussionmentioning
confidence: 99%
“…5,[13][14][15] However, there are few studies that compare the effect of calcineurin inhibitors on oxidant and an antioxidant system indices in kidney transplant recipients. [16][17][18][19][20] The purpose of this prospective study was to evaluate the effects of the calcineurin inhibitors tacrolimus and cyclosporine on cardiovascular disease risk factors, including high-sensitivity CRP (hsCRP), homocysteine, malondialdehyde (MDA, a lipid peroxidation biomarker of oxidative stress), and activity of PON and arylesterase (components of the antioxidant system), in kidney transplant recipients.…”
mentioning
confidence: 99%